The Effect of Teacher Motivation on Student Achievement in Islamic Senior High School - Pratomo, Herdianto Wahyu; Kuswati, Yeti (Qualitative and Quantitative Research Center, 2022)
Improving the quality of education can be seen in the success of formal education in the form of student achievement. A learning process in the activities determines student achievement carried out by teachers and students. The purpose of this study was to determine the significant influence of teacher motivation on learning achievement at Islamic Senior High Schools statistically. This research used the associative quantitative method to determine the effect or relationship between two or more variables. This research place is at the Islamic Senior High School of Nurussyahid, Kertajati, Majalengka, Indonesia. The number of samples is a total sampling of 18 teachers. The result shows that implementing teacher work motivation in Islamic Senior High School Nurussyahid can be categorized as good. The achievement of Islamic Senior High School of Nurussyahid students can be categorized as good. Implementing teacher work motivation has a positive and significant effect on student achievement. The success or failure of a student's achievement in Islamic Senior High School of them is determined by the provision of motivation by teachers.